2014
DOI: 10.1186/1471-2458-14-454
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ preferences for vaccinating daughters against human papillomavirus in the Netherlands: a discrete choice experiment

Abstract: BackgroundTo generate knowledge about potential improvements to human papillomavirus (HPV) vaccination information and organization strategies, we assessed how aspects of HPV vaccination are associated with parents’ preferences for their daughters’ uptake, and which trade-offs parents are willing to make between these aspects.MethodsA discrete choice experiment (DCE) was conducted among parents with a daughter aged 10–12 years. Panel mixed logit regression models were used to determine parents’ preferences for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 35 publications
(47 reference statements)
1
45
0
Order By: Relevance
“…Our results are consistent with the reported responses for other vaccines in the literature, thereby providing evidence of face validity. 16,19,21 Among the leptospirosis vaccine attributes, efficacy had the greatest impact on acceptability. Current leptospirosis vaccines with 70-100% efficacies are more likely to be accepted if introduced in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the reported responses for other vaccines in the literature, thereby providing evidence of face validity. 16,19,21 Among the leptospirosis vaccine attributes, efficacy had the greatest impact on acceptability. Current leptospirosis vaccines with 70-100% efficacies are more likely to be accepted if introduced in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about the safety of HPV vaccination and potential long-or short-term side effects were reported by an average of 43% of hesitant study participants. [23][24][25][26][27][28][29]31,32,[34][35][36][37][38]40,42,46,49,[70][71][72][73][74][75][76][77][78][79][80][81] Fear of side effects was reported by an average of 52% of general study participants 51,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] and 17% of favourable study participants. 25,37,71 Concerns about si...…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Across all studies, an average of 34% of hesitant participants were found to doubt the effectiveness of the vaccine, 23,24,26,32,34,37,[73][74][75]77,114 as well as 39% of general participants 43,46,82,[84][85][86]96 and 3% of favourable participants. 26,37 Perceived low vaccine effectiveness was particularly prevalent among hesitant participants in studies in Spain (2013, 66%), 112 the Netherlands (2009, 57%), 26 and Italy (2006-2014, 37%).…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by drawing inferences from individuals’ stated choices, DCEs produce estimates of respondent preferences that are less subject to biases introduced when individuals are asked to explicitly report and assess the motivations underlying their choices [ 15 ]. Within the health services literature, DCEs have been used to elucidate patient preferences ranging from human papillomavirus vaccination among adolescent females [ 16 ] ,to treatment of osteoarthritis among older adults [ 17 ], and linkage to HIV care services among the general population [ 18 ]. However, few DCEs have examined HIV testing preferences in low or middle income countries (LMIC) [ 19 23 ] or among MSM.…”
Section: Introductionmentioning
confidence: 99%